High-Energy Proximal Humerus Fractures in Geriatric Patients: A Review - Jordan M. Walters MD; Shahryar Ahmadi MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
High-energy proximal humerus fractures in elderly patients can occur through a variety of mechanisms, with falls and MVCs being common mechanisms of injury in this age group. Even classically low-energy mechanisms can result in elevated ISS scores, which are associated with higher mortality in both falls and MVCs. These injuries result in proximal humerus fractures which are commonly communicated via Neer’s classification scheme. There are many treatment options in the armamentarium of the treating surgeon. Nonoperative management is widely supported by systematic review as compared to almost all other treatment methods. ORIF is particularly useful for complex patterns and fracture dislocations in healthy patients. Hemiarthroplasty can be of utility in patients with fracture patterns with high risk of AVN and poor bone quality risking screw cut-out. Reverse total shoulder arthroplasty is a popular method of treatment for geriatric patients also, with literature now showing that even late conversion from nonoperative management or ORIF to rTSA can lead to good clinical outcomes. Prevention is possible and important for geriatric patients. Optimizing medical care including hearing, vision, strength, and bone quality, in coordination with primary care and geriatricians, is of great importance in preventing fractures and decreasing injury when falls do occur. Involving geriatricians on dedicated trauma teams will also likely be of benefit.